QOE measurement model in wi-fi networks: Analysis of socioeconomics influences in Indonesia - Ruliyanta; Ahmad, Mohd Riduan; Awang Md Isa, Azmi (Wydawnictwo SIGMA-NOT, 2024)
We measure the quality-of-service level of the existing Wi-Fi network on the office in Indonesia. Next, the user is asked to measure the level of network experience. We compare the results of our experience assessment survey with the system's quality of service. The method we use is to group volunteers into two socio-economic groups. The assessment results were carried out using an artificial neural network algorithm. Observation results show that the average quality of service in Socio 1 is 87,11%, while in Socio 2, 92.45%. The mean absolute percentage error measurement results we obtained statistically for Socio 1 were 3.54%, and for Socio 2, the value was 2.11%. The Mean absolute percentage error using artificial neural network backpropagation in Socio 1 is 4.02%, while in the Socio 2 group is 2.06%. The relationship between the two results shows a heavy correlation.